Assessment of one-way shear design method of IS-456:2000 - Bansal, Sahil; Kumar, Pawan (Journal of Structural Engineering, 2024)
For decades, the shear carrying capacity of Reinforced Concrete (RC) members has been studied both experimentally and analytically by researchers worldwide. Despite all the efforts by the researchers, the shear resistance mechanisms of RC members remain a complicated and debated phenomenon. As a result, different codes around the world have their shear design provisions based on different experimental and theoretical grounds. The study is categorized into two parts. First, the adequacy of the one-way shear design method of Indian Standard (IS)-456 in predicting the shear strength of RC members without and with stirrups is assessed, and second, the safety level associated with the existing one-way shear design method is examined. The uncertainty associated with the material properties, fabrication factor, and analysis method is considered in this study. The reliability analysis is performed for a combination of dead and imposed load values. The findings of this study exemplify the need for a new shear design method that offers a more uniform level of conservativism for all the factors influencing shear strength, as well as reliability analysis-based calibration for shear strength design with a higher level of uniformity in terms of safety and efficiency.